Semiotic Analysis Of Visual Signs Found in Main Bosses’ Cutscenes Of Elden Ring Video Game - I Kadek Bagaskara Cahaya Dhanadipa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study examines the interpretation of verbal and visual signs in the cutscenes of the video game Elden Ring. Semiotics, the study of signs and their meanings, provides the framework for analyzing these cinematic elements. Video games often embed narrative clues within visual and verbal signs, but players frequently overlook them, particularly during cutscenes, which interrupts gameplay to deliver critical story content. This research focuses on the main boss cutscenes in Elden Ring, which integrate environmental storytelling and visual signs to convey the lore of The Lands Between. Utilizing Peirce’s theory of signs and Barthes’ theory of meaning, the study identifies and classifies visual signs—icons, indices, and symbols—within the cutscenes to interpret their narrative significance. The data is derived from eight main boss cutscenes recorded during gameplay and supplemented by external visual references. A qualitative approach was employed, encompassing data collection through documentation, detailed visual analysis, and descriptive presentation of findings. Results indicate that Elden Ring’s cutscenes are rich with embedded signs that enhance the storytelling experience, though their nuanced meanings often require active interpretation and community discussion. This research underscores the importance of cutscenes in contributing to the depth and immersion of the game’s narrative.